Pengaruh Bauran Pemasaran terhadap Kinerja Pemasaran melalui Keunggulan Bersaing pada Produk Rokok Andalan - Fitrie, Bella Nur; Respati, Harianto (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to examine the influence of the marketing mix on marketing performance through competitive advantage in the context of cigarette products, specifically the Andalan brand. The research was conducted at PT Bintang Sayap Utama, a subsidiary of Gudang Baru Group, located in Kepanjen, Malang. Using a quantitative approach, data were collected from 100 marketing staff selected through simple random sampling. The data were analyzed using statistical methods with the assistance of SPSS software. The research findings indicate that the marketing mix has a significant effect on both marketing performance and competitive advantage. Furthermore, competitive advantage was also found to have a positive effect on marketing performance. However, the indirect effect of the marketing mixon marketing performance through competitive advantage was not statistically significant. This suggests that while competitive advantage enhances marketing outcomes, it does not mediate the relationship between the marketing mix and marketing performance in this case. The study contributes to the literature by highlighting the direct role of marketing mix elements product, price, place, and promotion in enhancing marketing performance in the tobacco manufacturing industry. The results provide valuable insights for companies in highly competitive markets to focus on optimizing their marketing strategies to directly improve performance outcomes.